Research Trends of Gamification in Science Learning Over the Decade and the Impact in Physics - Isnaini Agus Setiono; Lasiani (Universitas Negeri Semarang, 2026)
The physics learning environment often causes cognitive load on students. Designing a physics learning environment that is friendly to students’ cognitive load is a challenge for teachers. This study aims to analyze research topics on gamification in science learning and its impact on physics over the past decade. This research was conducted through bibliometric analysis, combined with a literature review. Data obtained from Scopus publications. The research trend on gamification in science learning increased over the decade, from 2016 to 2025. The United States is the country with the most publications on this topic. The 125 publications in conference papers represent the largest number of publications on this topic. The most frequently used keywords, based on network analysis, include gamification, computer science education, science education, STEM education, augmented reality, and computer-aided instruction. Gamification in science learning has a positive impact on physics. Gamification has an impact on increasing student engagement and creativity, motivation and interest in learning, in-depth understanding of concepts, and self-efficacy. The results of this study provide insight into the need for further research on gamification innovations in physics concepts and on the design of digital technologies for gamification-based physics learning.